2021
DOI: 10.1017/s0007114521000660
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Mediterranean-Dietary Approaches to Stop Hypertension Intervention for Neurodegenerative Delay diet with cardiac remodelling in the community: the Framingham Heart Study

Abstract: Normal cardiac function is directly associated with the maintenance of cerebrovascular health. Whether the Mediterranean-Dietary Approach to Systolic Hypertension Intervention for Neurodegenerative Delay (MIND) diet, designed for the maintenance of neurocognitive health, is associated with cardiac remodeling is unknown. We evaluated 2512 Framingham Offspring Cohort participants who attended the 8th examination cycle and had available dietary and echocardiographic data (mean age 66 years; 55% women). Using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 46 publications
(66 reference statements)
2
31
0
1
Order By: Relevance
“…On the contrary, an inverse association between the MIND diet and global circumferential strain (GCS) among subjects, aged >66 years was reported. 27 Our findings were in agreement with a new study that demonstrated an inverse association between higher adherence to the MIND diet and the odds of stroke (OR: 0.41; 95% CI: 0.18 to 0.94) in adults. 28 However, there are some differences between the latter study and the current study.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, an inverse association between the MIND diet and global circumferential strain (GCS) among subjects, aged >66 years was reported. 27 Our findings were in agreement with a new study that demonstrated an inverse association between higher adherence to the MIND diet and the odds of stroke (OR: 0.41; 95% CI: 0.18 to 0.94) in adults. 28 However, there are some differences between the latter study and the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Physical activity [123][124][125][126][127][128][129][130][131][132][133][134][135] and MIND (Mediterranean-DASH Intervention for Neurodegenerative Delay) diets. [144][145][146] A systematic review 147 of the use of supplements, including vitamins C, D and E, omega-3 fatty acids and ginkgo biloba, found little to no benefit in preventing cognitive decline, MCI or Alzheimer's dementia.…”
Section: Cardiovascular Disease Risk Factors Physical Activity and Dietmentioning
confidence: 99%
“…A heart‐healthy diet emphasizes fruits, vegetables, whole grains, fish, chicken, nuts, legumes and healthy fats such as olive oil while limiting saturated fats, red meat and sugar. Examples of heart‐healthy diets are the Mediterranean, DASH (Dietary Approaches to Stop Hypertension) and MIND (Mediterranean‐DASH Intervention for Neurodegenerative Delay) diets 144–146 …”
Section: Overviewmentioning
confidence: 99%
“…A future direction in the food industry can be functional food, which shapes the intestinal microbiota to a health-promoting composition. A varied, homemade, fruit- and vegetable-rich Mediterranean diet has similar health-promoting effects on the microbiota ( 179 181 ).…”
Section: Effects Of Nutrition On Intestinal Permeability and The Gut ...mentioning
confidence: 99%